2014
DOI: 10.1200/jco.2013.54.7844
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Subsequent Malignant Neoplasms in Long-Term Hereditary Retinoblastoma Survivors After Chemotherapy and Radiotherapy

Abstract: A B S T R A C T PurposeHereditary retinoblastoma (Rb) survivors have increased risk of subsequent malignant neoplasms (SMNs). Previous studies reported elevated radiotherapy (RT) -related SMN risks, but less is known about chemotherapy-related risks. Patients and MethodsIn a long-term follow-up study of 906 5-year hereditary Rb survivors diagnosed from 1914 to 1996 and observed through 2009, treatment-related SMN risks were quantified using cumulative incidence analyses and multivariable Cox proportional hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
97
4
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 54 publications
8
97
4
2
Order By: Relevance
“…94 However, a population-based study in England suggested that 35% of bilaterally affected patients had a family history. 9 In three population-based studies 9,11,95 representing 2,738 retinoblastoma patients on three continents, 30–37% of cases were bilateral. When we add the 15–18% of unilateral cases who also carry an RB1 mutant allele, approximately 45% of people with retinoblastoma carry one RB1 mutation in their constitutional cells.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…94 However, a population-based study in England suggested that 35% of bilaterally affected patients had a family history. 9 In three population-based studies 9,11,95 representing 2,738 retinoblastoma patients on three continents, 30–37% of cases were bilateral. When we add the 15–18% of unilateral cases who also carry an RB1 mutant allele, approximately 45% of people with retinoblastoma carry one RB1 mutation in their constitutional cells.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…144 Acute toxicities of IVC for retinoblastoma are as for other paediatric cancers, including short-term transient pancytopenia (reduction in red blood cells, white blood cells and platelets), hair loss, vincristine-induced neurotoxicity, and infections. Long term toxicities include carboplatin-induced ototoxicity (high tone hearing loss) in some patients, 145 second non-ocular cancer risk with alkylating agents 95,146 and secondary acute myeloid leukaemia following intense chemotherapy including topoisomerase inhibitors, doxorubricin and alkylating agents. 147,148 …”
Section: Managementmentioning
confidence: 99%
“…12 In addition, survivors of hereditary retinoblastoma who received radiation therapy for their primary tumor have an elevated risk of developing a secondary sarcoma lesion in the radiation field. 13 Approximately 1% of patients who survive childhood cancer develop treatment-related bone cancer within 20 years of their primary therapy. 14 Patients treated with radiation therapy for a prior malignancy have a ninefold higher risk of developing a secondary Approximately 1% of patients who survive childhood cancer develop treatment-related bone cancer.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Although these data are encouraging, longer follow-up is needed (26). Another study demonstrated increased risk of bone tumors and leiomyosarcoma for those treated with alkylating agent chemotherapy plus radiotherapy (including ERBT and brachytherapy) versus radiotherapy alone (27). Together, these studies demonstrate the importance of surveillance for second primary tumors among patients with hereditary RB, and the need to better understand the relationship of specific therapies and clinical risk factors associated with these malignancies.…”
Section: Hereditary Rb: Introductionmentioning
confidence: 99%